Population genetic structure of the freshwater fish, barbonymus schwanenfeldii (BLEEKER) in several river system in Malaysia - Khoo, Andy Han Guan. (Universiti Malaysia Sarawak (UNIMAS), 2004)
ABSTRACT Studies on the genetic variation of Barbonymus schwanenfeldii (Bleeker 1853) populations from Malaysia were done using partial sequencing of cytochrome b mtDNA gene. This study examines 450 base pairs of the mitochondrial DNA cytochrome b sequences from 23 samples of fishes from the genus Barbonymus, a group of primary freshwater cyprinids known to inhibit the Southeast Asia region. Sampling were carry out for various locations throughout Sarawak while as a comparison; a few samples of B. schwanenfeldii were taken from Peninsular Malaysia like Serting River, Negeri Sembilan by using PCR-RFLP analysis and DNA sequence analysis of cytochrome b mtDNA gene. Phylogenetic relationship inferred using neighbor-joining (NJ) and parsimony methods generally divided samples into two major clades, consistent with their geographic origin: one group of B. schwanenfeldii which locally known as Lampam sungai are samples from Peninsular Malaysia while another group clustered B. schwanenfeldii which locally known as Tengadak are samples from Sarawak but including some individual from Peninsular Malaysia. PCR-RFLP analysis showed no polymorphism between samples of B. schwanenfeldii fish from Peninsular Malaysia and B. schwanenfeldii from Sarawak. In general, this study indicated that DNA sequence analysis has potential advantages over PCR-RFLP analysis of cytochrome b mtDNA gene in detection of even small genetic variation, or synonymous substitution between samples. The low level of gene flow (Nm = 0.61) and high population structuring (Fsi = 0.449) between Peninsular Malaysia and Sarawak could be correlated with the separation of Borneo Island from mainland Peninsular during Pleistocene Epoch, which occur about 10,000 years ago. Interestingly, some samples from Peninsular Malaysia clustered together within the Sarawak clades.